Pesticides in Surface Waters: Distribution, Trends, and Governing Factors - Larson (CRC Press, 2009)
Pesticde use in agriculture and non-agriculture settings has increased dramatically over the last several decades. Concern about adverse effects on the environment and human health has spurred an enormous amount of research into their environmental behavior and fate. Pesticides in Surface Waters presents a comprehensive summary of this research. This book evaluates published studies that focus on measuring pesticide concentration. The studies chosen include peer reviewed scientific literature, government reports, laboratory studies, and those using microcosms and artificial streams and ponds. The authors used this information to develop their overview of pesticide contamination of surface waters. The exhaustive compilation of data along with the fundamental science make this book essential for those involved in pesticide use, environmental protection, water quality, and human or ecological risk assessment. Pesticides in Surface Waters covers the results of actual studies, sources of pesticides to surface water, fate and transport, and environmental significance. Hundreds of data-packed tables, maps, charts, and drawings illustrate the key points, making research and application easy and cost effective.